Is war a good or a bad thing: Children's attitudes towards war - Kuterovac-Jagodić, Gordana (Array, 1997)
It has been documented that childrens basic attitudes towards social questions are formed during the early school-age period. Besides the influence of parents, who play the most important role it that period, other sources of information like personal experiences, peers, school and media become increasingly more important in attitude formation as a child grows older. As a part of a pilot study of a larger project concerning the long-term effects of war on childrens psychological health and development, Punamäkis attitude scale towards war was administered (Punamäki, 1987). The scale consists of 21 items clustered in four scales: a) Moral judgment of war in general, b) Justification of the own nations fight, c) Personal loyalty and the sense of duty in a state of war and d) Attitudes to the possibility of peace. The aim of the study was to examine attitudes of Croatian children after the war was ceased and to explore the relationship between the attitudes and childrens gender, age and amount of their experiences with war and violence. Sample consisted of 230 Croatian children aged from 11-14 years who are attending schools in Zagreb. Childrens war experiences were examined by the Questionnaire on childrens Stressful and Traumatic War Experiences (Franc, Kuterovac and Stuvland, 1993). The obtained data indicate that children's sex and war experiences are more related to their attitudes towards war than age. The results will be discussed in the light of earlier studies and compared to findings obtained with the same scale on children in Israel.